C-Reactive Protein, Lipid Profile and Body Mass Index in Patients of Liver Cirrhosis (Bangladesh Journal of Infectious Diseases, 2022)
Background: Liver cirrhosis leads to the abnormalities in liver function.Objective: This study aimed to determine the C-reactive protein (CRP) and lipid profile in cirrhotic patients as well as their correlation with patients age and body mass index.Methodology: This case- control study was conducted in the Chittagong Medical College Hospital and People’s Hospital Limited, Chattogram from October 2017 to March 2018 for a period of six months. Venous blood was collected from 25 patients and 25 controls after 8 hours overnight fasting. Inflammatory marker (CRP) and Serum lipid status were recorded for each participant.Results: The mean serum C-reactive protein; total cholesterol; Triglycerides; High Density Lipoprotein and Low Density Lipoprotein level were 2.448 ± 1.174; 132.228 ± 15.352; 100.228 ± 20.564 mg/dl; 53.081 ± 9.994 mg/dl and 59.108 ± 18.634 mg/dl in cirrhotic patients. CRP value was significantly higher in patients compared to healthy individuals (p < 0.05). The extent of decreasing lipid profile (except HDL) was also significantly related to the progress in cirrhosis (p < 0.05). The positive correlation of age and BMI of patients were associated with CRP and various lipid variables.Conclusion: The higher CRP value and extent of decreasing lipid profile (except HDL) in patients may serve as a baseline for further studies that required to determine the predictive values of lipid profiles as a means to estimate the extent of liver damage in cirrhotic patients.Bangladesh Journal of Infectious Diseases June 2021;8(1):27-31